Strategi Kampanye Stop Pernikahan Usia Anak Desa Sidomulyo Kecamatan Ngadirojo Kabupaten Pacitan - Resti Wulansari; Oksiana Jatiningsih (Universitas Negeri Surabaya (Unesa), 2023)
This study reveals about the campaign for child marriage in Sidomulyo Village, Ngadirojo District, Pacitan Regency, namely the village strategy in how to build public awareness not to do child marriage. The purpose of the study was to describe strategies to build public awareness and implement a campaign to stop child marriage in Sidomulyo village, Ngadirojo district, Pacitan district. The theory used in this research is Paulo Freire's Critical Education Theory which suggests that the liberation of the illiterate poor to be able to read, then decides to increase it to critical consciousness or public awareness of the problems they face. In the case of child marriage, awareness is meant to provide an understanding of the dangers posed by child marriage from the educational, economic and health aspects. This study uses a qualitative research approach that produces descriptive data with a critical study research design or critical research involving researchers directly to participate in the implementation of the stop child marriage campaign activities, which means researchers participate in raising public awareness of the understanding of the Marriage Act, Law Child Protection and the dangers posed by child marriage. The results of the study indicate that the concept of conscientization or realizing public awareness that focuses on problem posing education regarding cases of child marriage is realizing FGD in the form of dialogue between the community and resource persons so that awareness can run optimally with the aim of the community not doing and rejecting age marriage. children, but the awareness-raising conducted through the FGDs has not run optimally because it still tends to provide information from one party and the dialogical process has not been achieved as expected. Keywords: strategy, campaign, child marriage